Synthesized nano particles of glimepiride via spray freezing into cryogenic liquid: characterization, antidiabetic activity, and bioavailability - Dalia A. Gaber; Abdulrahman S. Alhuwaymili; Hessah S. Alhawas; Alhnouf A. Almutiri; Amal M. Alsubaiyel; Siham A. Abdoun; Reem A. Almutairi (Taylor & Francis Group, 2022)
The aim of this work was to formulate glimepiride (class II drug) which is characterized by low solubility and high permeability as nanostructured particles using a cryogenic technique with an aid of water-soluble polymer to improve its aqueous solubility and hence its bioavailability. 27 formula of glimepiride nano size particles were prepared by a spray freezing into cryogenic liquid (SCFL) using poly vinyl pyrrolidone K-30 (PVP K-30); that three drug polymer ratio (1:1, 1:2, and 1:3), with three different volumes of feeding solution (50, 100, 150 mL), at three flow rates (10, 20, and 30 mL/min). The prepared formulations were evaluated for production yield, particle size, zeta potential, drug content, release rate, in vivo hypoglycemic activity, and bioavailability. All prepared formulations showed high production yield and drug content ranged between 91.1 ± 3.4% and 94.3 ± 1.8% and 95.1 ± 2.8% and 97.1 ± 2.5%, respectively. The mean particles size was ranged between 280 ± 62 nm and 520 ± 30 nm. The results of in vitro release study revealed significant enhancement in the solubility of prepared formulations compared with the pure drug. It was found that optimal formula showed a significant reduction in blood glucose levels in diabetic rats, and 1.79-fold enhancements in oral bioavailability compared with market tablets. Nanoparticle prepared by SCFL method is an encouraging formula for improving the solubility and the bioavailability of glimepiride.